Sustainable infrastructure principles into practice - Ainger, C.M. (Charles M.); Fenner, Richard (Richard A.) (Delivering sustainable infrastructure, 2014)
The Delivering Sustainable Infrastructure series is a new series of practical handbooks which provide engineers with an understanding of sustainability principles and solutions. Sustainability concepts are set within well-known engineering management processes of planning, designing and delivering infrastructure. The first book in the Delivering Sustainable Infrastructure series, Principles into Practice sets out a framework of fundamental principles, methodologies and approaches, with numerous practical examples from real civil engineering projects.